Efficacy and efficiency of auditory discrimination procedures for children with autism spectrum disorder and typical development: A preliminary investigation. Issue 1 (2nd January 2021) - Bergmann, Samantha; Kodak, Tiffany; Van Den Elzen, Gabriella; Jones, Terra; Benitez, Brittany
ABSTRACT: An auditory discrimination involves differential behavior in the presence of auditory stimuli due to a history of reinforcement. A dearth of research on the instruction of auditory discrimination is in the behavior-analytic literature, so identifying strategies to teach this skill is necessary. This might be especially pertinent for individuals diagnosed with autism spectrum disorder (ASD) with impaired auditory discrimination repertoires. The current study evaluated the efficacy and efficiency of go/no-go, do this/do that, and auditory match-to-sample on the acquisition of novel auditory discrimination tasks with three children with ASD and two children of typical development in a total of ten comparisons. At least one condition was efficacious for all participants. The do this/do that procedure was more likely to be efficacious and efficient compared to go/no-go and auditory match-to-sample.